Attachment forces of pea aphids (Acyrthosiphon pisum) on different legume species. (21st July 2015) - FRIEDEMANN, KATRIN; KUNERT, GRIT; GORB, ELENA; GORB, STANISLAV N.; BEUTEL, ROLF G.
Abstract : 1. Sympatric populations of insects adapted to different host plants are good model systems not only to study how they adapt to the chemistry of their food plant, but also to investigate whether morphological modifications evolved enabling them to live successfully on a certain plant species. 2. The pea aphid, Acyrthosiphon pisum (Harris) encompasses at least 11 genetically distinct sympatric host races, each showing a preference for a certain legume species. The leaflet surfaces of these legumes differ considerably in their wax coverage. 3. It was investigated whether the attachment structures of three pea aphid genotypes from different host races are adapted to the different surface properties of their host plants and whether they show differences in their attachment ability on the respective host and non‐host plants. 4. The surface morphology of plants and aphid tarsi was examined using SEM (scanning electron microscopy). The ability of the aphids to walk on specific surfaces was tested using traction force measurements. 5. The presence of wax blooms on the leaflets lowers the aphids' attachment ability considerably and diminishes their subsequent attachment on 'neutral' surfaces like glass. The pea aphid host races differ in their ability to walk on certain surfaces. However, the genotype from the adapted aphid host race was not necessarily the one with the best walking performance on their host plant. All aphids, regardless of the original host plant, were most efficient on the neutral control surface glass. The general host plant Vicia faba was the plant with the most favourable surface for all aphid host races.